GAYA KEPEMIMPINAN DALAM MENDUKUNG PERILAKU ORGANISASI DI PT. KERRY INGREDIENTS INDONESIA PADA MASA PANDEMI COVID-19 - Ismie Fauziah Sutisna (Pendidikan Ekonomi FKIP Universitas Sriwijaya, in partnership with Asosiasi Profesi Pendidikan Ekonomi Indonesia (ASPROPENDO), 2020)
This study is to determine the leadership style and work environment that support organizational behavior in PT. Kerry Ingredients Indonesia. This research method uses qualitative methods by conducting interviews between leaders and employees, with questions about organizational behavior during the current pandemic. From the research results that the leadership style in supporting organizational behavior at PT. Kerry Ingredients Indonesia during the Covid-19 pandemic, the leader ordered his employees to do work from home (WFH) and also the leader applied the established health protocol, namely wearing a mask when indoors or outdoors. As well as carrying out social distancing to break the chain of spread and transmission of covid-19.